Advances in Synthesis and Applications of Self-Healing Hydrogels - Fan, Leqi; Ge, Xuemei; Qian, Yebin; Wei, Minyan; Zhang, Zirui; Yuan, Wei-En; Ouyang, Yuanming (Frontiers in Bioengineering and Biotechnology, 2020)
Background Hydrogels, a type of three-dimensional (3-D) crosslinked network of polymers containing a high water concentration, have been receiving increasing attention in recent years. Self-healing hydrogels, which can return to their original structure and function after physical damage, are especially attractive. Some self-healable hydrogels have several kinds of properties such as injectability, adhesiveness, and conductivity, which enable them to be used in the manufacturing of drug/cell delivery vehicles, glues, electronic devices, and so on. Main Body This review will focus on the synthesis and applications of self-healing hydrogels. Their repair mechanisms and potential applications in pharmaceutical, biomedical, and other areas will be introduced. Conclusion Self-healing hydrogels are used in various fields because of their ability to recover. The prospect of self-healing hydrogels is promising, and they may be further developed for various applications.